Enhancing Student Learning Outcomes of Simulation Materials for Throwing Competitions Utilizing the Group Investigation Method Among Class X-9 Students at SMA Negeri 1 Sukomoro Academic Year 2023/2024 - Ni’mah, Aulia Safrotun; Nuraffandi, Dimas; Refdianingrum, Nada Putri; Kuntjoro, Bambang Ferianto Tjahyo; Suwarto, Edi Tjahyo (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. This study aimed to assess the enhancement of student learning outcomes in the shot put simulation material by employing the Group Investigation method among class X-9 students at SMA Negeri 1 Sukomoro during the 2023/2024 Academic Year. Materials and Methods. Engagements and insights. Contemplation andThe objective of the students in class X-9 at SMA Negeri 1 Sukomoro is reflected in the practical test results and the observation sheets documenting the teaching and learning activities. This study employs Classroom Action Research (CAR) involving 34 subjects for investigation. learner. Results. The findings of the study indicated that the learning outcomes of PJOK regarding the shot put simulation material, when implemented through the Group Investigation model in class X, demonstrated improvement. This was evidenced by the learning outcomes in cycle I, where 61.76% of students achieved learning completion, which rose to 88.23% in cycle II. Conclusion. The results indicate a notable improvement in learning outcomes. Therefore, it can be concluded that the Group Investigation learning model effectively enhances the learning outcomes of PJOK in the shot put simulation material for class X students at SMA Negeri 1 Sukomoro during the 2023/2024 academic year. This study demonstrates that the Group Investigation method effectively enhances active participation and student learning outcomes, albeit necessitating additional time and careful oversight. Individual evaluations may also be influenced by the performance of the group.